Faktor-Faktor yang Mempengaruhi Jumlah Tindak Kriminal di Sumatera Utara Tahun 2022 - Dunda, Abduroqy Alimarwan; Purwoto, Agus; Choirunnisa, Asyifa; Falah, Raihan Ainurrahim; Putri, Resti Yulianda (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The problem of crime is an issue that often occurs in various countries, including Indonesia. This research aims to obtain a general picture of the number of criminal acts in North Sumatra Province, identify the factors that influence the number of criminal acts, and determine the magnitude of the contribution of influential variables. Analysis was carried out on crime data in North Sumatra using Multiple Linear Regression Analysis. The research results show that the GRDP variable has a significant effect on the number of crimes. While the variables Percentage of Poor Population, TPT, and Population Density do not have a significant effect on the number of crimes, it is hoped that the results of the research will provide a deeper understanding of the factors that influence crime in North Sumatra and help in formulating prevention policies that are more targeted.